Egbert Jamieson & Francis Adams, The Municipal Code of Chicago 303-04 (1881) - (:unkn) unknown (My University, 1881)
§ 1276: Prohibited any vessel laden in whole or in part with gunpowder or gun-cotton shall land or make fast to any dock or wharf upon the Chicago river, or either branch thereof between the school section and Chicago avenue, or discharge such gunpowder or gun-cotton within said limits. Violators shall be fined not less than twenty nor more than one hundred dollars.
Keywords: GUNPOWDER - TRANSPORTATION